The EVerT2 (Effective Verruca Treatments 2) trial: a randomized controlled trial of needling vs. nonsurgical debridement for the treatment of plantar verrucae. (1st November 2017) - Hashmi, F.; Fairhurst, C.; Cockayne, S.; Cullen, M.; Bell, K.; Coleman, E.; Harrison‐Blount, M.; Torgerson, D.
Summary: Background: Verrucae are a common foot skin pathology, which can in some cases persist for many years. Plantar verrucae can be unsightly and painful. There are a range of treatment options including needling. Objectives: The EVerT2 (Effective Verruca Treatments 2) trial aimed to evaluate the clinical and cost‐effectiveness of the needling procedure for the treatment of plantar verrucae, relative to callus debridement. Methods: This single‐centre randomized controlled trial recruited 60 participants (aged ≥ 18 years with a plantar verruca). Participants were randomized 1 : 1 to the intervention group (needling) or the control group (debridement of the overlying callus). The primary outcome was clearance of the index verruca at 12 weeks after randomization. Secondary outcomes included recurrence of the verruca, clearance of all verrucae, number of verrucae, size of the index verruca, pain and participant satisfaction at 12 and 24 weeks. A cost‐effectiveness analysis was carried out from the National Health Service perspective over 12 weeks. Results: Sixty eligible patients were randomized (needling group n = 29, 48%; debridement group n = 31, 52%) and 53 were included in the primary analysis (needling n = 28, 97%; debridement n = 25, 81%). Clearance of the index verruca occurred in eight (15%) participants (needling n = 4, 14%; debridement n = 4, 16%; P = 0·86). The needling intervention costs were on average £14·33 (95% confidence interval 5·32–23·35) more per patient than for debridement. Conclusions: There is no evidence that the needling technique is more clinically or cost‐effective than callus debridement. The results show a significant improvement in pain outcomes after needling compared with the debridement treatment alone.